The Influence of Service Quality and Marketing Strategy on Purchasing Decisions of One Point Computer Shop Stores in Bengkulu City - Fahmi Ridho Ansori; Muhamad Galy Njoman Ari Pribowo (Journal of Indonesian Management, 2023)
The title of this research is the effect of Service Quality and Marketing Strategy on the Purchasing Decisions at One Point Computer Shop Bengkulu City. This study aims to know the effect of service quality and marketing strategy on the purchasing decision at one point computer shop Bengkulu city. The research was conducted from September to December 2022. The sample of this research is consumers of One Point Computer Shop Bengkulu City with the total number 130 people. The sampling technique used is probability sampling. The method used inthis study is a quantitative method with Multiple Linear Regression analysis using SPSS 24 for windows. Based on the results of multiple linear regression, the following equation is obtained: Y = 1.295 + 0.685 (X1) + 0.100 (X2), the research results and hypotheses in this study indicate that service quality (X1) and marketing Strategy (X2) has a positive and significant effect both partially and simultaneously on purchasing decisions (Y) at the One Point Computer Shop Bengkulu City.